A provisional checklist of banana cultivars in Uganda - Karamura, D.A.; Karamura, E.B.; International Network for the Improvement of Banana and Plantain (1994)
The purpose of this study was to determine the variation pattern that exists in the East African Highland bananas (Musa AAA) grown in Uganda, estimate levels of dissimilarity caused by different growing conditions, and establish a flexible provisional classification and identification system. Techniques of numerical taxonomy were employed to determine the variation pattern and these included two different coefficients, three different clustering methods, principal component analysis and classificatory discriminant analysis. Sixty-one morphological characters were employed to determine differences among the 238 accessions available for the study. 192 accessions were from the national banana germplasm collections, 46 were from farmers' fields in selected sites. Four categories have been adopted in the classification of the East African Highland bananas : group, subgroup, clone set and clone. Five clone sets were delineated, based mainly on qualitative characters. Beer and Musakala were very distinct from each other and from the rest of the clone sets. Nakabululu, Nfuka and Nakitembe were least distinct from each other.